Beyond Maternal Mortality: A Systematic Review of Evidences on Mistreatment and Disrespect During Childbirth in Health Facilities in India. (October 2021) - Jungari, Suresh; Sharma, Baby; Wagh, Dhananjay
The aim of this systematic review is to examine current evidence on the nature and extent of disrespect and abuse (D&A), mistreatment and practices of respectful maternity care of women during childbirth in India. Electronic databases were searched for published studies relevant to the topic. The search was conducted from May to September 2018. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to conduct the review. A results synthesis was done using the Bowser and Hill landscape analytical framework for D&A of women during childbirth. Eleven studies are included in this review of which six were cross-sectional, four were qualitative, and one used a mixed-method approach. The type of abuse most frequently reported was the lack of respect and dignity (nondignified care) experienced by the women, usually in the form of negative and unfriendly attitudes of the providers. The least frequent form of mistreatment was physical abuse and detention in the facilities. The frequency of reported D&A was high, ranging from 10% to 77.3%. These behaviors were influenced by lack of education and empowerment of the women, their low socioeconomic status, poor training of providers and supervision, and a lack of accountability. Overall, disrespectful and abusive behavior had adverse impact on the utilization of health facilities for childbirth. It created a psychological distance between women and health providers. To our knowledge, this is the first systematic literature review to be conducted on respectful maternity care in India.